Pembebanan Hak Tanggungan dalam Pemberian Kredit pada Lembaga Perkreditan Desa (LPD) - I Nyoman Agus Saputra; I Nyoman Putu Budiartha; Ni Gusti Ketut Sri Astiti (Jurnal Konstruksi Hukum, 2021)
In 1984, the Provincial Government of Bali issued an idea to assist Pakraman villages in carrying out cultural functions. Through Governor's Letter Number 972 of 1984, November 1, 1984 concerning Village Credit Institutions. This study aims to explain the system of providing credit to village credit institutions with guarantee of mortgage rights and to explain legal remedies against customers who do not carry out the obligations as outlined in the credit agreement. This research was designed with normative research, the source of legal materials consisted of primary and secondary legal materials. Analysis of legal materials through interpretation analysis. The results of the study show that the provision of credit to village credit institutions with guarantees of mortgage rights is stated in the credit agreement between the LPD and customers who are required to also receive approval from the customary Bendesa, in this case to apply customary sanctions when bad credit occurs. Customary sanctions are the last resort after other efforts are unsuccessful with the aim that credit arrears can be paid back and bad credit customers do not carry out the obligations as outlined in the credit agreement are given sanctions for confiscation of collateral bound by imposition of mortgage rights for immovable objects. Of course this is adjusted to the regulation of the Governor of Bali Province Number 44 of 2017 binding on the imposition of mortgage rights in providing credit to the LPD which only applies to local customary villages, in this case the LPD is a savings and loan business entity owned by a traditional village.